Selection and Identification of Potential Hydrolytic Bacillus from Litter Composting - Ika Setianingsih; Nisa Rachmania Mubarik; Iman Rusmana (Jurnal Ilmu Pertanian Indonesia, 2026)
Microbe study on degraded trash has been widely conducted, with the intention of improving the efficiency and effectiveness of waste processing. The purpose of this study was to select and identify hydrolytic Bacillus from litter composting. The samples were the litter composting outcomes with five different treatments, namely the inclusion of nutrient broth (NB), commercial formula, molasses, tryptic soy broth (TSB), and talcum, with each formula containing a microbial consortium. Bacteria were isolated using the serial dilution method. Each isolate was evaluated for its capacity to lyse red blood cells on blood agar media. Cellulolytic, amylolytic, and proteolytic bacteria were grown on nutritional agar media containing carboxy-methyl cellulose (CMC), starch, and skim milk. The antagonistic test involved testing isolates that hydrolyze all three types of substrates. Isolates that were not antagonistic to one another were identified based on phenotypes (colony and cell morphology using Gram staining) and genotypes (16S rRNA gene). Fourteen isolates of Bacillus sp. had cellulolytic, amylolytic, and proteolytic properties. Four isolates were chosen; two of them were comparable to Bacillus stercoris, while the other two, 5.5 and 5.9R, are similar to Calidifontibacillus erzurumensis and Bacillus amyloliquefaciens. Therefore, litter can be used to determine the hydrolytic capability of Bacillus isolates. Keywords: amylolytic, Bacillus, cellulolytic, proteolytic